PENGGUNAAN LIMBAH ABU KAYU HALABAN SEBAGAI BAHAN TAMBAHAN SEBAGIAN SEMEN PADA CAMPURAN BETON - Jovan Perdhana; Bambang Wedyantadji; Vega Aditama (Institut Teknologi Nasional Malang, 2022)
Halaban wood ash is the result of chemical changes from the process of burning Halaban wood with a fire of about ±1000ºC and it takes about 150 minutes to turn the wood lump cells into ash. Halaban wood ash contains silica which is a good aggregate binder and is quite high, so it has pozzolanic properties. This study aims to determine the effect of adding ash from burning halaban wood on the mechanical properties of concrete and also knowing the optimum percentage of halaban wood ash from 0%, 5%, 10%, 15% in terms of compressive strength of concrete, split tensile strength of concrete and flexural tensile strength. concrete. The method used in this study is the DOE (Design Of Experiment) method using a cylindrical specimen with a diameter of 15 cm and a height of 30 cm for testing the compressive strength of concrete, beams with a size of 15 cm x 15 cm x 62 cm for testing the flexural strength. The test object was made with 4 variations of the composition of Halaban Wood Ash as a concrete testing material, namely 0%, 5%, 10%, 15% by weight of cement. Testing of the specimens was carried out at the age of 28 days. The number of test objects as many as 64 pieces. Based on the research conducted, it is known that there is no effect in increasing the strength of concrete with the addition of halaban wood ash on the mechanical properties of concrete. This is indicated by the decrease in the results of testing the compressive strength, split tensile strength, and flexural tensile strength of normal concrete with a mixture of halaban wood ash. And the absence of the optimum percentage of Halaban wood ash from 5%, 10%, 15% in terms of the compressive strength of concrete, split tensile strength of concrete and flexural tensile strength of concrete.